Movement Kinematics and Interjoint Coordination Are Influenced by Target Location and Arm in 6-Year-Old Children - Bagesteiro, Leia B.; Balthazar, Rogerio B.; Hughes, Charmayne M. L. (Frontiers in Human Neuroscience, 2020)
Rapid aiming movements are typically used to study upper limb motor control and development. Despite the large corpus of work in this area, few studies have examined kinematic manual asymmetries in children who have just started formal schooling and until now, none have characterized the manner in which children coordinate their joints to complete these movements (i.e., interjoint coordination). In the present study, manual asymmetries in kinematics and interjoint coordination in strongly right-handed 6-year-old children were investigated when reaching for ipsilateral and contralateral targets with their dominant right arm and the non-dominant left arm. Overall, manual asymmetries in interjoint coordination are apparent for both 6-year old children and young adults, although young children completed the task by adopting a different strategy than adults. In addition, control strategies employed by 6-year-old children were influenced by both the location of the target as well as the arm used to perform the task. Specifically, compared to all other conditions, children’s trajectories were more curved when performing contralateral movements with the non-dominant left arm, which were driven by smaller shoulder excursions combined with larger elbow excursions for this condition. Based on these results, we argue that the differences in interjoint coordination reflect the stage of development of 6-year-old children, the origin of which derives from maturational (e.g., hand dominance) and environmental factors (e.g., school-based experience).